Enhanced corrosion resistance of high strength Mg-3Al-1Zn alloy sheets with ultrafine grains in a phosphate-buffered saline solution - Kim, H. S.; Kim, G. H.; Kim, H.; Kim, W. J. (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
The corrosion behaviour of ultrafine grained AZ31Mg alloy sheets with very high strength, which were prepared by high-ratio differential speed rolling (HRDSR) technique, was studied in a phosphate-buffered saline solution. The corrosion resistance was greatly improved after HRDSR. This result was attributed to the enhanced stability of the Mg(OH)(2) layer due to the grain refinement and precipitation of various types of P-containing compounds on the stabilised Mg(OH)(2) layer. The HRDSR technique has a good potential to be used for the development of magnesium sheets with good combination of mechanical and biocorrosion properties. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: MAGNESIUM ALLOY; BEHAVIOR; DEFORMATION